About People and Bees: theory and practice in the handling of the concept of culture in managerial contexts (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4026.95-121On people and bees. Theory and practice in usage the concept of culture in managerial contexts: We applied comparative method between culture and organizational culture concepts, each one, originated in the anthropology and in the general theory of administration, respectively. This dialogue explains theoretical differences and application’s particularities, possibilities and limits from each different concept, when in practical situations. It suggests complementing the functionalist approach from administrative hegemonic approaches, with other conceptual elements present in the local structures of the action contexts. Finally, we suggest a way of doing it, effectively, through some theoretical and methodological development incorporation from social sciences which has demonstrated, through empirical research, the possibility of seizure the cultural dynamics in the most diverse study locus. It sets up, then, in a collaborative effort among several areas of applied social sciences.